Análise do uso dos sinais de pontuação em produções escritas do ensino médio - Becher, Tatiane Cristina (2019)
Portuguese language teaching involves the practice of reading and writing throughout the entire school education process. Even so, there are constant difficulties presented by students at different grade levels when interpreting and/or writing a text, which reflects the permanent need for academic research and proposals for teaching practices related to the area. One of the recurring difficulties demonstrated by the students is the use of specific mechanisms of written language such as textual punctuation. This research presents an investigative overview focused especially on the use of punctuation in written compositions. The object of study was defined through the application of an initial investigative writing proposal, applied in two public schools in the region, through which punctuation was discovered as one of the biggest difficulties in the writing of high school students, especially in the use of comma and period. With the intention of contributing to Portuguese Language teaching, this research’s main objective is to investigate the use of punctuation marks in written compositions of high school students, in order to verify the most recurrent problems of incomprehension of punctuation marks by these students and to raise hypotheses on how to work with these occurrences in the classroom to lead the student to understand the different functions of textual punctuation. Hence, an answer to the following question is sought: how do students use the punctuation marks in their texts, especially the dot, the period and the comma, when receiving epilingual activities and written composition proposals? This study is theoretically based on the premises of Linguistics and Applied Linguistics, being classified as a quantitative-qualitative, ethnographic research in education, action-research, exploratory, involving both practice and theory related to punctuation, by investigating the theme, developing a didactic unit to use in the classroom and analyzing the results of this work’s application through quantitative surveys and qualitative analyzes, therefore through a mixed method. The theoretical contribution is based on authors such as Halliday and Hasan (1976), Pécora (1983), Bakhtin (1992), Corrêa (1994), Chacon (1996), Geraldi (1997), Cunha and Cintra (2003), Bronckart (2003), Rajagopalan (2003), Koch (2003, 2008, 2010), Dahlet (2006), Marcuschi (2008), Brocardo and Costa-Hübes (2009) and Cunha and Saleh (2013). Theoretical basis involves matters pertinent to punctuation in its syntactic-semantic, rhythmic-prosodic and cohesive aspect, seeking to reflect on the different roles that can be performed by punctuation marks in the written text. In the corpus analysis, the punctuation problems perceived were mainly related to the absence of punctuation marks. In other words, students generally tend not to punctuate their texts, which may be justified by the lack of understanding of the various aspects that involve the role of punctuation and reflects the need and pertinence of further studies on the subject.